For a N th polynomial which satisfy f ( i ) = ( i N + 1 ) 1 for i = 0 , 1 , 2 , … , N , what is the sum of the possible outcomes of f ( N + 1 ) ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We are trying to find the degree N polynomial f ( X ) such that f ( j ) = ( j N + 1 ) − 1 0 ≤ j ≤ N This polynomial is uniquely defined, and is given by Lagrange Interpolation as f ( X ) = j = 0 ∑ N π j ( j ) f ( j ) π j ( X ) where π j ( X ) = k = j 0 ≤ k ≤ N ∏ ( X − k ) 0 ≤ j ≤ N Now π j ( j ) π j ( j ) f ( j ) π j ( N + 1 ) = k = j 0 ≤ k ≤ N ∏ ( j − k ) = ( − 1 ) N − j j ! ( N − j ) ! = ( N + 1 ) ! j ! ( N + 1 − j ) ! π j ( j ) − 1 = ( − 1 ) N − j ( N + 1 ) ! N + 1 − j = k = j 0 ≤ k ≤ N ∏ ( N + 1 − k ) = N + 1 − j ( N + 1 ) ! for all 0 ≤ j ≤ N , and so f ( N + 1 ) = j = 0 ∑ N π j ( j ) f ( j ) π j ( N + 1 ) = j = 0 ∑ N ( − 1 ) N − j = j = 0 ∑ N ( − 1 ) j = { 1 0 N e v e n N o d d so the sum of possible values of f ( N + 1 ) is 0 + 1 = 1 .
Problem Loading...
Note Loading...
Set Loading...
Here’s an elementary approach to solve this problem (no lagrange interpolation, nothing).
The key idea here is the connection of f ( i ) with f ( i − 1 ) ,
which is,
f ( i − 1 ) f ( i ) = ( i N + 1 ) ( i − 1 N + 1 ) = N + 2 − i i .
Now, after re-arranging,
( N + 2 − i ) f ( i ) − i f ( i − 1 ) = 0 .
The expression on the left side is an ( N + 1 ) t h polynomial and has N roots.
( N + 2 − i ) f ( i ) − i f ( i − 1 ) = α ( i − 1 ) ( i − 2 ) ⋯ ( i − N ) ( i − r ) ,
where r represents the root we don’t know about.
Now, this might seem unsolvable because it has not one but two unknowns, but, really, it is not. (You actually have a lot to exploit here!)
First of all, put i = 0 ,
( N + 2 ) = ( α ) ( r ) ( − 1 ) N + 1 ( N ! ) .
Now, put i = N + 2 ,
− ( N + 2 ) f ( N + 1 ) = ( α ) ( ( N + 1 ) ! ) ( N + 2 − r ) .
For one last time, put i = N + 1 ,
f ( N + 1 ) − 1 = ( α ) ( N ! ) ( N + 1 − r ) .
Now, using the first equation to substitute α for r in the last two and equating the resulting expressions of f ( N + 1 ) , we get,
( − 1 ) N + 1 r ( N + 2 ) ( N + 1 − r ) + 1 = − ( − 1 ) N + 1 r ( N + 1 ) ( N + 2 − r ) .
Now,
r = N + 1 , N is even.
r = N + 2 , N is odd.
Now, it’s not hard to see that f ( N + 1 ) is 1 and 0 accordingly as N is even and odd.